1995
DOI: 10.1007/bf02253373
|View full text |Cite
|
Sign up to set email alerts
|

Genetic vs. environmental contributions to human handedness: Insights gained from studying individuals with unilateral hand injuries

Abstract: Four hundred eleven individuals who had suffered temporary unilateral hand injuries were assessed on five hand preference behaviors after their recovery. Measures of shifts to contralateral hand use experienced during and after the recovery period were taken. The best predictor of hand use shifts during the injury recovery period was whether the injury was to the preferred or nonpreferred hand. The incidence of postinjury contralateral shifts was low but was greater than that observed over a simulated injury p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…Contrary to what would be expected due to the decrease in fine motor control with age (Smith et al, 1999), the later life group did not show a significantly lower amount of improvement in legibility. Studies using MRI scans have shown that older individuals tend to recruit more cortical areas during learning than younger individuals, thereby compensating for any possible loss in fine motor control (Johansson, 2004).…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Contrary to what would be expected due to the decrease in fine motor control with age (Smith et al, 1999), the later life group did not show a significantly lower amount of improvement in legibility. Studies using MRI scans have shown that older individuals tend to recruit more cortical areas during learning than younger individuals, thereby compensating for any possible loss in fine motor control (Johansson, 2004).…”
Section: Discussioncontrasting
confidence: 84%
“…In learning new simple tasks, such as finger tapping, the non-preferred hand will improve its performance with training, but it will not reach or exceed the level of skill of the preferred hand. Other studies (Chapman & Henneberg, 1999;Galobardes, Berbstein, & Morabia, 1999;Porac, 1995), found that it is possible for the non-preferred hand to be trained to write as legibly as with the preferred one. This was further strengthened by Teixeria and Paroli (2000), who found no difference in simple motor task control, strength, or positioning between the preferred and non-preferred hand and arm.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…However, this type of genetic-environment interaction analysis is useful in attempting to account for the manifest complexities of human handedness types. Porac (1995aPorac ( , 1995b argued that life experience factors must be taken into account by genetic theories because these influences are meaningful forces in the formation of hand preference side and strength. It is also possible that genetic determination of human hand preference is more complex than that conceptualized in several of the most prominent contemporary models (Annett, 1985;Coren, 1994Coren, ,1995bMcManus, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and familial influences, as well as social and cultural factors,20 have been considered to underlie handedness. Better skill performance in one hand can be seen as a training effect from more frequent use of one hand.…”
Section: Discussionmentioning
confidence: 99%